Gerald D. Schmidt & Larry S. Roberts' foundations of parasitology - Roberts, Larry S (McGraw Hill, 2000)
This excellent text which is now in its 6th edition is probably the best general coverage of the science of parasitology available. I teach parasitology at the university level, which means that I have surveyed the competition. For completeness, abundance of relevant illustrations, and well-written coverage, this book is the best I have seen.